Expression and matrix deposition of latent transforming growth factor β binding proteins in normal and fibrotic rat liver and transdifferentiating hepatic stellate cells in culture - Breitkopf-Heinlein, Katja; Lahme, Birgit; Tag, Carmen G.; Gressner, Axel M. (Hepatology, 2001)
Latent transforming growth factor β binding protein (LTBP), a high-molecular-weight glycoprotein of the large latent TGF-β complex is suggested to serve as an anchor for latent TGF-β in the extracellular matrix and as a component of microfibrillar structures. Proteolytic cleavage of LTBP is supposed to be a prerequisite for the release and generation of bioactive (mature) TGF-β. We investigated the expression of LTBP isoforms in normal and fibrotic rat liver and in cultured rat hepatic stellate cells (HSC) transdifferentiating to myofibroblasts (MFB). We further determined their interaction with the matrix and some of their basic functions. Immunostainings of normal and fibrotic livers demonstrate intense signals for LTBP-1 and -2, preferably in parenchymal, but also nonparenchymal, cells and in fibrotic extracellular matrix. However, in situ hybridization points to a restriction of transcripts to nonparenchymal cells from fibrotic livers, whereas hepatocytes were always devoid of LTBP transcripts. The findings were confirmed by real-time quantitative reverse-transcription polymerase chain reaction (RT-PCR), which showed isoform-specific increases of LTBP transcripts in cultured stellate cells transdifferentiating to MFB and by Northern blot analyses showing the absence of LTBP-1 mRNA in freshly isolated hepatocytes. Using a cell enzyme-linked immunosorbent assay (ELISA), a differential increase of partly deoxycholate (DOC)-resistant, matrix-bound LTBP-1 and -2 was measured in cultured stellate cells. Treatment with plasmin generated soluble LTBP-1 and bioactive TGF-β, which was able to induce Smad7 expression in an autocrine fashion. Our data propose (transdifferentiating) stellate cells, respectively MFB, as the major source of LTBP in normal and fibrotic liver, which here probably fulfills structural and TGF-β-regulating functions as suggested for nonhepatic tissues.
Elektronische Reproduktion der Druck-Ausgabe
First published: 30 December 2003
Gesehen am 23.06.2022